2018
DOI: 10.1186/s12868-018-0481-5
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin contributes to the injury development and neurological deficit after acute subdural hemorrhage in rats only in collaboration with additional blood-derived factors

Abstract: BackgroundAcute subdural hemorrhage (ASDH) is a severe consequence of traumatic brain injury. The occurrence of subdural blood increases the lethality of these patients independent of the amount of blood or elevated intracranial pressure. Thrombin is one of the potential harmful blood components. Possible harmful effects of thrombin are mediated via the Protease-activated-receptor-1 (PAR1) and thus, translating the acute Thrombin release after ASDH into cell loss. The objectives of the present study were twofo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 72 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…These injuries may be caused not only by the pressure of the hematoma but also by the influence of blood components ( 15 ). Other studies have indeed found that thrombin in blood and some components in blood clots are factors causing brain swelling and other serious consequences ( 16 18 ). Therefore, studying the role of cerebral circulation in ASDH will be conducive to a comprehensive understanding of the pathophysiological changes after ASDH.…”
Section: Discussionmentioning
confidence: 93%
“…These injuries may be caused not only by the pressure of the hematoma but also by the influence of blood components ( 15 ). Other studies have indeed found that thrombin in blood and some components in blood clots are factors causing brain swelling and other serious consequences ( 16 18 ). Therefore, studying the role of cerebral circulation in ASDH will be conducive to a comprehensive understanding of the pathophysiological changes after ASDH.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, intracerebral infusion of a low dose of thrombin activates endogenous neuroprotective mechanisms and increases tolerance to cerebral ischemia. In case of a considerable increase thrombin intensifies edema and secondary lesion of the brain after ischemia and hemorrhages [8,14,15]. Instillation of thrombin іn vitro in nanomolar and micromolar concentrations induces death of the cells in the culture of the hippocampus and motor neurons [16].…”
Section: Materials and Methods Of The Studymentioning
confidence: 99%
“…Thrombin, a serine protease and an essential component of the coagulation cascade, displays proinflammatory response in neurodegeneration [3–5]. Further studies indicate that protease‐activated receptors (PARs) mediate the toxic effects of thrombin on diseases in the central nervous system [6,7], and PAR‐1 is a high‐affinity receptor for thrombin in brain. Earlier reports indicate that an increase in PAR‐1 leads to neuronal damage caused by cerebral ischemia [8,9].…”
Section: Introductionmentioning
confidence: 99%